Is there a “Meditative-polemic-May”? - Maruszka Eve-Marie Meinard (LingBaW)
This article aims at displaying the results of a preliminary study on MAY and MIGHT in extraposed subject clauses where they compete with the meditative-polemic-Should. Two types of extraposed subordinate clauses will be compared, one in which MAY and MIGHT have an epistemic meaning and one in which they behave like the meditative-polemic-Should. The examples extracted from Google reveal that this specific use of MAY and MIGHT is mostly found in American English, that it is mostly used in journals, and that the subclause refers to past events that could logically be expected. What is more, the subordinate clause containing this modal auxiliary reformulates the title of the article or of a paragraph. This shows that the proposition in which it is found plays a crucial role in the text, which is to provide the main information of the article once the background has been explained. We will also see that when the subject of the content clause is animate, MAY and MIGHT are less likely to have an epistemic or root reading than when the subject is inanimate. Finally, the examples reveal that this form collocates with subjective markers denoting the point of view of the subject, via the use of verbs of cognition and perception or via the progressive aspect (it’s not surprising that he may want, need, choose, be feeling…). We propose to call it the “subjective-explanatory-May”.